REVEALING DAYANG SUMBI’S SHAMEFUL SIDES AND QUESTIONING THE MORAL VALUE OF THE LEGEND OF SANGKURIANG - Cahya Pratama Windianto (Universitas Gunadarma, 2022)
Indonesia’s folklore has been categorized as parts of sacred legacy. As parts of legacy, they contain moral values which have been passed down through many generations. Therefore, since they have been told and given from one generation to the next generation, societies universally agree that the moral values must not be questioned. Sangkuriang, as an example of folklore, also contains sacred moral value which must be agreed widely and not be criticized. The moral value of the legend of Sangkuriang says that a son must not marry his mother. This moral value is agreed by most Indonesian readers. It is largely approved that Sangkuriang’s mother, named Dayang Sumbi, is struggling and must be supported by the readers. On the other hand, readers have been told to disagree with Sangkuriang. However, by paying close attention, readers can actually find some violence done by Dayang Sumbi and illogical values written within the story of Sangkuriang which ironically have been widely agreed and recognized as universal moral values which must be followed by the society of Indonesia. This paper reveals that Dayang Sumbi is not a role model by applying the Transitivity theory as the linguistic evidences to show her shameful sides. To question and criticize the moral values, the writer applies Derrida Deconstruction. Since this paper aims to describe and analyze the findings in a narrative form, the writer applies qualitative research method. Based on the findings, there were some shameful sides shown by Dayang Sumbi and illogical values within the story.